Analisis Kepatuhan Syariah dalam Praktik Bisnis Network Marketing Studi Kasus: PT Bandung Eco Sinergi Teknologi (PT BEST) - Muhammad Azkal Aulia; Meyga Nurcahyo Usfantoro; Aurel Imdaduloh; Jaenudin J; Dian Herdiana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The rapid growth of multi-level marketing (MLM) companies in Indonesia, including those claiming to adopt a sharia-based system, raises questions regarding the conformity of their business mechanisms with Islamic economic law principles. This study aims to analyze the level of sharia compliance in the network marketing practices of PT Bandung Eco Sinergi Teknologi (PT BEST). A qualitative approach with a descriptive-analytical method is employed to examine PT BEST’s business system based on muamalah principles and the provisions of DSN-MUI Fatwa No. 75/DSN-MUI/VII/2009 on Sharia-Compliant Multi-Level Direct Selling. Primary data were collected through interviews with distributors and management, observations of training and marketing activities, and documentation studies of company regulations and bonus schemes. The findings indicate that PT BEST has made efforts to implement a sharia-compliant network marketing model by providing real and beneficial products and explicitly avoiding riba-related practices. However, several aspects still require improvement, particularly the balance between product sales and member recruitment, the transparency of bonus distribution, and the effectiveness of sharia supervision. The study concludes that PT BEST’s business system partially fulfills sharia principles and offers recommendations for strengthening more ethical, transparent, and equitable network marketing practices.